Demographic Variables and Wealth Craving Tendencies Among Adolescents in OYO Town, Nigeria - Olagoke, Ogunlade Oludele; Oriyomi, Rabiu (MultiTech Publisher, 2024)
Despite various researches on dangers of illegal wealth craving among youths, the problem still persists even among both youth and old. Therefore, the present study considered Demographic variables in relation to wealth craving among adolescents in Oyo town, Nigeria. The study adopted a descriptive survey of expo-factor design because the problem is age long and still gaining more grounds beyond expected degree despite widespread of religion activities which preach moral and good values to their members. The instrument was validated and found to be appropriate to the present study. The results showed the respondents have moderate peer pressure, moderate societal attitude and a high wealth craving issue. There is a significant difference of students’ perception of wealth issue based on gender. There is no significant difference of students’ perception based on home type and finally, the finding revealed no significant difference of students’ perception of wealth craving issue based on religion. Based on the findings, following recommendations are provided: Counselling psychologists should be posted at various government establishment which include but not limited to schools, local government, state government and encourage to mount psychological interventions capable of promoting dignity of labour, values and right type of attitude towards good name. Parents should be sensitized on the need to monitor and correct their children with love when they observed them exhibiting antisocial behavior among others.